Genetic circuits in synthetic biology: broadening the toolbox of regulatory devices - Müller, Marik M.; Arndt, Katja M.; Hoffmann, Stefan A. (Frontiers in Synthetic Biology, 2025)
Devices sensing inputs and generating outputs are fundamental regulatory units, and as such are the basis of more complex regulatory networks. We provide an overview of regulatory devices used as fundamental regulatory building blocks in synthetic biology, and how complex genetic circuitry is being constructed from them. We first comprehensively explore devices operating at different levels of gene regulation, with action modes on the DNA sequence, to transcriptional, translational and post-translational control. We then discuss design principles of constructing genetic circuits from basic regulatory units, addressing challenges such as orthogonality, context-dependence, noise, and complexity. We present examples of genetic circuitry, including bistable switches, logic gates, signal amplification, memory devices and circuitry for biocomputation. How artificial genetic circuitry can be useful in real-life applications is illustrated with examples from bioproduction, living therapeutics, and biosafety. Our aim is to provide a comprehensive overview of the toolbox of regulatory devices and a profound understanding of their potential for constructing diverse genetic circuits and their applications.